(untitled) (Research, Society and Development, 2022)
Building materials normally change their properties when they are affected by high temperatures. This research analyzed the residual strength of ceramic blocks and cementitious mortars subjected to temperatures of 200, 400, 600 and 800ºC, in three test conditions: hot breakage, breakage after sudden cooling and breakage after slow cooling. There was a gain in compressive strength for the ceramic blocks when hot broken for all temperatures analyzed. However, for the cementitious mortars, there was a gain in strength only in compression for the temperature of 200°C when broken when hot, but for the other test conditions and temperatures, the strength was significantly reduced and showed a drop of around 70% for sudden cooling. at 600°C.